Rekonstruksi Aparatur Pemerintah Melalui Tahapan Literasi Digital E-Government Studi Kasus Pemerintah Kabupaten Maros - Nurdiansyah, Aldy; Nina Lestari; Nursaleh Hartaman (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2025)
This article examines the stages of e-Government implementation in Maros Regency, using qualitative methods with descriptive and exploratory approaches. This study focuses on observational data on the Maros Regency government website to reflect the extent to which local government digital services have been developed and navigated. Through observations of web features, such as information dissemination, public interaction, and service accessibility, this study identifies the current stages of e-Government adoption by various government agencies (OPDs) in the region. Data analysis was conducted using the Cart determination and World Bank reference data to ensure the alignment of Maros Regency's progress with international standards for e-Government implementation. The results show significant progress in web presence and interaction, but challenges remain in the full integration of transactional services. This study highlights barriers, including limited digital infrastructure and low literacy rates among government staff and the public, that hinder the optimization of e-Government services. In addition, this report provides recommendations for strengthening digital literacy and improving technological infrastructure to improve public service connectivity in the region. Overall, this study underlines the potential of e-Government to increase transparency, efficiency, and public participation in government processes in Maros Regency.